STRATEGI HUMAS DP3APPKB SURABAYA DALAM UPAYA MENINGKATKAN KESADARAN HIDUP SEHAT REMAJA - Tiara Saktiwi, Denisa Putri; Rini Ganefwati; Delmarrich Bilga Ayu Permatasari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2025)
The high number of physical and mental health disorders among Surabaya teenagers requires an appropriate communication strategy from government institutions, especially in building awareness of the importance of healthy living. This study examines the public relations strategy implemented by the Surabaya City Women's Empowerment, Child Protection, Population Control, and Family Planning Agency (DP3APPKB) in an effort to increase awareness of healthy living among teenagers. The research approach used was qualitative descriptive with a case study method. Data were collected through in-depth interviews, field observations, and documentation, then analyzed using the four-stage public relations strategy model from Cutlip, Center, and Broom, namely: research, planning, implementation, and evaluation. The results of the study showed that the DP3APPKB public relations strategy included the use of social media, community-based educational campaigns, active involvement of GenRe Ambassadors as agents of change, and a participatory interpersonal approach. This strategy succeeded in increasing adolescent participation in promotive and preventive activities related to physical and mental health. These findings reinforce the importance of the role of government public relations in shaping healthy adolescent behavior through adaptive and innovative public communication.